Pelatihan Sistem Pertanian Cerdas Berbasis Internet of Things di Desa Kaasar, Minahasa Utara: Training on Internet of Things-Based Smart Farming System in Kaasar Village, North Minahasa - Afrioni Roma Rio; Andi Ikhtiar Bakti; As'ari As'ari; Jumriadi Jumriadi; Rachma Rahim (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The smart farming system training based on the Internet of Things (IoT) in Kaasar Village, North Minahasa, North Sulawesi, successfully enhanced farmers' understanding and skills in operating smart farming technology. The pre-test results indicated that 80% of participants were unfamiliar with the technology, but after the training, 90% demonstrated a good understanding of how to use the system. Additionally, the training on business strategy and digital marketing improved farmers' skills in promoting their products through Google Business and social media. However, some challenges were encountered, such as the limited number of devices available, which required participants to take turns using them. This program has had a significant positive impact on the sustainability of agricultural businesses in Kaasar Village, although some technical aspects need improvement to enhance the effectiveness of future training sessions.